New development cycle through long-term investment ? - Romain Dittgen (EchoGéo)
Gabon’s recent ambition to reduce its dependency on oil revenue by diversifying its economy coincides with China’s growing investment in resource-rich African countries. Within the wide range of Sino–Gabonese co-operation, the mining sector – and above all the Bélinga iron ore project – is central to both parties’ interests. Omar Bongo’s regime promoted this large-scale project as the flagship of the national economy. However, despite the promise of infrastructure development and employment opportunities, Gabon’s attempt at diversification seems limited and is not leading towards any major structural change. A number of issues have challenged the realisation of the Bélinga project and introduced new risks and costs for the Chinese. These include commodity price volatility, the death of president Omar Bongo in 2009 and increasing dissent among civil society. The paper reviews development opportunities linked to the the Bélinga project and analyses China’s evolving approach towards the project.